National Indigent Criminal Defense Survey, 1982 ([Verlag nicht ermittelbar], 1986)
This survey was conducted to provide national-level data on basic information such as system types, funding sources, costs, and caseloads of indigent defense programs for defense practitioners, policymakers, and planners in the criminal justice system. The goal of the survey was to provide data that could begin to answer questions regarding the nature and scope of indigent service delivery. Specifically, the three basic objectives were to provide descriptive data, to assess the level of response to defense service delivery requirements, and to facilitate further research.